Preclinical Modeling of DCD class III Donation and Evaluation of the Most Adapted Preservation Protocol: Paving the Way for the Increased Use of this Challenging Donor Type. (July 2018) - Soussi, David; Rod, Xavier; Kerforne, Thomas; Thuillier, Raphael; Barrou, Benoit; Hauet, Thierry
Abstract : N/A: Current organ shortage imposes the need to expand the donor pool. Deceased after circulatory death (DCD) donors are a promising source, and in particular the Maastricht class III (arrest subsequent to cessation of life support in the hospital). While current results from class III are positive, the unavoidable expansion of inclusion criteria will severely impact organ quality and increase the complication rate. It is thus of paramount importance to study this donor type in a controlled model in order to explore preservation protocols and be ready for future challenges. We endeavored to reproduce the clinical conditions of DCD class III in the Large White pig and used this novel model to compare the performances of machine and static preservation protocols. Through a combination of: -pharmacological calcium blockers and chronotropes; -decreased ventilation; and -animal positioning; we successfully reproduced the conditions of DCD class III in a large animal, obtaining perfusion pressures and functional warm ischemia (hypoperfusion) levels on par with situations encountered in the clinic. Important functional and histological impacts were recorded. Organs from these animals were then collected and preserved through 3 protocols for 24h: static preservation (University of Wisconsin), machine preservation (Lifeport), static (20h) combined to machine (4h). Isotransplanted animals were then followed for 3 months. Preliminary findings indicate that the level of damage withstood by the organs could not be compensated by machine perfusion alone. An extended analysis will be presented and exploration of alternative preservation protocols will be discussed. This model could be invaluable to investigate new management alternative for extended criteria class III DCD donors, such as normothermic regional circulation and/or pharmacological supplementation. Figure. No caption available.